Anti-tumor Potential Ethnomedicinal Plants from Dayak Tribes in Central Kalimantan - Liswara Neneng; Asri Pujirahadju; Ferayani Ferayani; Tri Widayat (Biosaintifika: Journal of Biology & Biology Education, 2020)
Hornstedtia conica Ridl., Microsorum pustulatum Copel and Rourea fulgens Planch were medicinal plant used by  people of Dayak Tribes in Central Kalimantan for anti-tumor medicines. Although these plants has been widely used in traditional medicine, however, research and scientific evidence about their potential as anti-tumor are still very limited.  The research aims were to determine the qualitative content of phytochemical compounds and to study anti-tumor potential of these medicinal plants. This study used female Swiss Webster albino as a test animal.  Induction of tumor cell in mice used 7,12-Dimethylbenz [a] anthracene (DMBA), was done 10 times for 5 weeks.  Experiments were carried out used hexane extract from medicinal plants, every day for 7 weeks. The data obtained were analyzed descriptively. The results as follows: extracts of Hornstedtia conica Ridl., and Microsorum pustulatum Copel. contained alkaloids, while extract of Rourea fulgens Planch. contained flavonoids and saponins. All of these plant extracts were able to reduce the size and number of mice tumors. Hexane extract of H. conica was able to reduce the tumor size faster than another plants extracts. Mortality rate of mice in hexane extracts of H. conica and R. fulgens were zero- and in hexane extract of M. pustulatum it was 30%, meanwhile almost all mice in control group were died in days 15 of treatment. Based on this study, it can be concluded that hexane extract of H. conica and R. fulgens are potential as anti-tumor medicinal plants. These findings scientifically proved the potential of medicinal plant extracts as anti-tumor compounds.  H. conica is the most potential one for further development as alternative drug for inhibited of tumor growth.